Uso, manejo e estrutura da vegetação da caatinga por duas comunidades quilombolas do município de Jeremoabo, Bahia, Brasil - Almeida, Vanusa Sousa (2011)
Research in the field of ethnobotany, principally quantitative, with quilombola communities are still scarce, especially in Bahia, one of the states that represents the largest quilombola communities in the country (678 communities). Local knowledge about the use and diversity of plant resources in the quilombola communities of Casinhas e Baixa dos Queles, located in the municipality of Jeremoabo, Bahia, aimed to verify the culturally important species, their patterns of use, and relate them to the structural descriptors of the local vegetation. For this we used the quantitative and qualitative methods of ethnobotany, together with the methods of the ecological study of vegetation. 46 collaboratores in the two communities were interviewed to determine the local value of the plant species, as well as 12 local specialists in the B. Dos Quelés community. These groups were interviewed to determine which plant species were the most culturally prominent. The inclusion criterion for participating in the study was: to be quilombola, at least eighteen years old and to have lived in the quilombola region for at least ten years. For the study of phytosociology, 2 areas were selected. The first area included an area of greater intensity of use (area 1) and the other of little human impact (area 2) in the community B. Dos Queles. The point quadrant method was applied with inclusion of all species that have the DNS (diameter at ground level) ≥ 3 cm and height ≥ 1 m They were cited eighty-six plant species by the collaboratores of both communities, distributed among 36 families and 60 types. These species are used as medicine (75.6%), ritual or religious (22.1%), construction (19.8%), food (15.1%), fuel (9.3%), veterinary (5 8%), honey (5.8%), forage (4.6%), handicrafts (1.2%) and marketing (1.1%). The five species that had the highest local value by community, in descending order were: Casinhas - Gochnatia oligocephala (Gardner) Cabrera (Asteraceae) (candeia - 5,49), Hymenaea courbaril L. (Fabaceae) (jatobá - 3,87), Poincianella microphylla (Mart. ex G.Don) L.P.Queiroz (Fabaceae) (catingueira - 2,88), Lippia thymoides Mart. & Schauer (Verbenaceae) (alecrim - 2,70), Schinus terebentifolia Raddi (Anacardiaceae) (aroeira - 2,23), For the Baixa dos Quelés:: Gochnatia oligocephala (candeia - 4,83), Myrcia polyantha. DC. (Myrtaceae) (araçá preto - 4,07), Schinus terebentifolia (aroeira - 3,09), Mimosa tenuiflora (Wild.) Poir. (Fabaceae) (jurema-preta - 2,66), Cordia curassavica (Jacq.) Roem. & Schult. (Boraginaceae) (caatinga-de-cheiro - 2,59). Seventy-one species stood out in local therapy more culturally prominent. The five most prominent species are listed as follows: Gochnatia oligocephala (0.52), Cordia curassavica (0.37), Schinus terebentifolia (0.27), Mimosa tenuiflora (0.25 ), Lippia thymoides (0.23). Fourteen systems of disease were identified and the most common included the respiratory system (21.23%) and digestive system (20.54%) , they were the most frequent treatment with medicinal plants. The species Gochnatia Oligocephala was indicated in the local treatment of gastritis, Cordia curassavica to combat the symptoms of the common cold. Of the 64 species found in both forest environments, 32 species (50%) have recognized use and are grouped into nine categories of use. Leguminosae (sensu Engler) (9) and Myrtaceae (6) were the families with the greatest number of species. The category with the highest number of species was the medical (17) followed by fuel (13) and construction (8). Gochnatia oligocephala (candeia) and Pityrocarpa moniliformis (Benth.) Luckow & R. W. Jobson (quipé) were the species with the highest number of use, four each. Myrcia polyantha (araçá-preto) and Gochnatia oligocephala (candeia) had the highest IVI in the study of structure area 1 and together they hold 34.54% of IVI. These species are mainly used as fuel. The correlation analysis showed that the ecological parameters such as density (r=0.49,p<0.05), frequency (r=0.47,p<0.05), and importance value (r=0.58,p<0.05) were significaqnt and positive with the local value calculated for the plant species in the community of Baixa dos Quelés. The study of use, handling, and knowledge about plants by quilombolas, beyond recording and valuing the knowledge of these traditional communities, may be considered in public health policies aimed at meeting the needs of these populations and in the programs of local conservation.